2005
DOI: 10.1111/j.1365-2567.2005.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing dendritic cells become ‘lacy’ cells packed with fat and glycogen

Abstract: SummaryOn maturation, dendritic cells (DCs) become highly active cells equipped for antigen uptake, migration and clustering and activation of T cells. We therefore asked whether DCs acquire fat and glycogen stores as they mature. DCs were generated from mouse bone marrow stem cells by culturing with granulocyte-macrophage colony-stimulating factor (GM-CSF) for 7-8 days. Stimulation of the DCs with lipopolysaccharide (LPS) for the last 24 hr of culture, or exposure to 1-15 ng/ml of interleukin (IL)-4 during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…A similar placental phenotype has recently been reported in a baboon model of obesity (Farley et al 2009). It is also possible that maternal obesity may affect the number and function of other immune cell populations (Weisberg et al 2003, Maroof et al 2005, Macia et al 2006 at the maternal-fetal interface including natural killer cells and dendritic cells. Alterations in these cell populations could have lifelong implications for the fetal acquired immune system and disease susceptibility in later life (Challier et al 2008).…”
Section: Genementioning
confidence: 74%
“…A similar placental phenotype has recently been reported in a baboon model of obesity (Farley et al 2009). It is also possible that maternal obesity may affect the number and function of other immune cell populations (Weisberg et al 2003, Maroof et al 2005, Macia et al 2006 at the maternal-fetal interface including natural killer cells and dendritic cells. Alterations in these cell populations could have lifelong implications for the fetal acquired immune system and disease susceptibility in later life (Challier et al 2008).…”
Section: Genementioning
confidence: 74%
“…However the spleen plasmacytoid DCs contain very few well developed mitochondria and almost no rough endoplasmic reticulum (Figure 5 Panel B). In addition myeloid DCs from both lungs and spleen of OVA sensitized and challenged mice showed fat and glycogen stores which are typical characteristic of mature DCs (Maroof et al, 2005). Increased presence of mitochondria and rough endoplasmic reticulum indicates heightened cellular activity.…”
Section: Resultsmentioning
confidence: 98%
“…These stimulatory CD11c high MHC-II high CD19/B220 Ϫ cells therefore exhibit both functional and phenotypic hallmarks of conventional DCs (51,52). DCs were recently identified in older human omenta (17 adult donors aged 25-69 years, mean age of 53 years) (19), but walkout cells from omenta of 6-to 8-wk-old mice reportedly failed to stimulate in mixed lymphocyte reactions despite exhibiting some phenotypic properties of DCs (20). This discrepancy with our observations might have occurred if macrophages, or other myeloid cells with inhibitory activity in mixed lymphocyte reactions, were more prevalent in OFB of mice used in the latter study relative to mice used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid onset of CD69 expression described above indicated that Ag-presenting DCs might be present in the omentum, although previous studies have suggested that the omentum lacks DCs (8) based on both phentoypic (5, 9) and functional criteria (20). We therefore assessed the Ag presentation capabilities of OFB resident cells for their ability to activate naive allogeneic or male peptidespecific T cells.…”
Section: The Ofb Is a Site Of Rapid T Cell Activationmentioning
confidence: 99%